Abbott in darkness - Butler, D. J. (David John), 1973- (Baen Books, 2023)
"John Abbott is all in. He's up to his eyeballs in debt to pay for school, and he's just moved his small family forty light-years from Earth for a plum job with the wealthy interstellar corporation, The Sarovar Company. John's first assignment is to discreetly investigate possible corruption at the remote Arrowhawk Station, where Company traders buy the famous Sarovari Weave from the three-sided, crablike Weavers. John finds evidence of theft and worse, but when the guilty parties realize he's getting close, they come after him and his family. Can John catch the thieves and end their corrupt trade? Can he head off a war between the Company and the Weavers? Can he make a life for his family in this remote wilderness without corrupting himself? With no way back to Earth, the only direction for John Abbott and his family to go is forward--into danger"--